Assessment of groundwater quality and hydrogeochemical properties in the adrar continental intercalaire aquifer of the Algerian Sahara - Alia Sara Lakhdari; Boualem Bouselsal; Hakim Saibi; Mohammed Ouarekh (Applied Water Science, 2025)
Abstract Adrar, located in an arid desert environment in southwest Algeria, relies exclusively on groundwater from the Continental Intercalaire aquifer for its water supply. This study aims to assess the quality of this groundwater for human consumption, irrigation, and industrial use and identify the hydrogeochemical processes driving its mineralization. To achieve this, 18 wells were analyzed using conventional laboratory methods. Quality indices applied include the drinking water quality index for potability and the irrigation water quality index for agricultural suitability. Corrosion and scaling potential were evaluated using the Langelier index, Ryznar index, Larson–Skold index, Puckorius index, and aggressive index. The results indicate that 44.44% of the water is suitable for drinking, 50% is of medium quality, and 5.56% is unsuitable for drinking. For irrigation, 31.25% of wells provide good-quality water, while 68.75% are classified as doubtful. Most of the analyzed waters are corrosive, with a tendency toward scaling and CaCO3 precipitation. Hydrochemical analyses, including Piper diagrams, identified two water types: Ca–Mg–Cl (50%) and Ca–Cl (50%). Based on the Gibbs diagram, bivariate plots, and saturation indices, the groundwater’s mineralization is primarily attributed to water–rock interactions, such as the dissolution of silicate rocks, halite, and gypsum, along with cation exchange. Additionally, human activities significantly influence water chemistry. This study provides scientific foundations for sustainable groundwater resource management in Adrar, including water quality and exploitation. This work helps inform strategies for the preservation, rational use, and treatment of water, ensuring sustainable water access for domestic, agricultural, and industrial needs.